The symptomatology and diagnosis of domoic acid toxicosis in stranded California sea lions (Zalophus californianus): a review and evaluation of 20 years of cases to guide prognosis - McClain, Abby M.; Field, Cara L.; Norris, Tenaya A.; Borremans, Benny; Duignan, Pàdraig J.; Johnson, Shawn P.; Whoriskey, Sophie T.; Thompson-Barbosa, Lorraine; Gulland, Frances M. D. (Frontiers in Veterinary Science, 2023)
Introduction Domoic acid (DA) is a glutaminergic excitatory neurotoxin that causes the morbidity and mortality of California sea lions (Zalophus californianus; CSL) and other marine mammals due to a suite of effects mostly on the nervous and cardiac systems. Between 1998 and 2019, 11,737 live-stranded CSL were admitted to The Marine Mammal Center (TMMC; Sausalito, CA, USA), over 2,000 of which were intoxicated by DA. A plethora of clinical research has been performed over the past 20 years to characterize the range of toxic effects of DA exposure on CSLs, generating the largest dataset on the effects of natural exposure to this toxin in wildlife. Materials and methods In this study, we review published methods for diagnosing DA intoxication, clinical presentation, and treatment of DA-intoxicated CSL and present a practical, reproducible scoring system called the neuroscore (NS) to help assess whether a DA-affected CSL is fit for release to the wild following rehabilitation. Logistic regression models were used to assess the relationships between outcome (released vs. euthanized or died) and multiple variables to predict the outcome for a subset of 92 stranded CSLs. Results The largest proportion of DA-intoxicated CSLs was adult females (58.6%). The proportions of acute and chronic cases were 63.5 and 36.5% respectively, with 44% of affected CSL released and 56% either dying naturally or euthanized. The average time in rehabilitation was 15.9 days (range 0–169) for all outcomes. The best-performing model (85% accuracy; area under the curve = 0.90) assessing the relationship between outcome and predictor variables consisted of four variables: final NS, change in NS over time, whether the animal began eating in rehabilitation, and the state of nutrition on admission. Discussion Our results provide longitudinal information on the symptomatology of CSL intoxicated by domoic acid and suggest that a behavioral scoring system is a useful tool to assess the fitness for the release of DA-intoxicated CSL.